Self-education in the context of Rollo May's existential psychology and axiology - Zieliński, Paweł (Studia z Teorii Wychowania, 2024)
The author recognises the assumptions of Rollo May's philosophy and existential psychology and, in this context, investigates the essence of the pedagogical thought of the eminent American psychologist. In particular, he focuses on the process of self-education, which enables a person to live a creative and satisfying life. However, this is a difficult process, associated with experiencing crises, re-evaluating one's own value systems, dealing with fears and feelings of guilt. Without self-development understood in this way, a person will not discover the meaning of his or her own existence and will not be able to live authentically and realise his or her own potential. Becoming aware of the negative aspects of one's own nature and working through them is the key to self-realisation and even the development of non-egoistic forms of consciousness.